Down Syndrome Related Muscle Hypotonia: Association with COL6A3 Functional SNP rs2270669 - Dey, Arpita; Bhowmik, Krishnendu; Chatterjee, Arpita; Sinha, Swagata; Mukhopadhyay, Kanchan (Frontiers in Genetics, 2013)
Down syndrome (DS), the principal cause for intellectual disability, is also associated with hormonal, immunological, and gastrointestinal abnormalities. Muscle hypotonia (MH) and congenital heart diseases (CHD) are also frequently observed. Collagen molecules are essential components for maintaining muscle integrity and are formed by the assembly of three chains, alpha 1-3. The type VI collagen is crucial for cardiac as well as skeletal muscles. The COL 1 (VI) and 2 (VI) chains are encoded by genes located at the 21st chromosome and are expected to have higher dosage in individuals with DS. The  3 (VI) chain is encoded by the COL6A3 located at the chromosome 2. We hypothesized that apart from COL6A1 and COL6A2, COL6A3 may also have some role in the MH of subjects with DS. To find out the relevance of COL6A3 in DS associated MH and CHD, we genotyped two SNPs in COL6A3, rs2270669 and rs2270668, in individuals with DS. Subjects with DS were recruited based on the Diagnostic and Statistical Manual for Mental Disorders-IV and having trisomy of the 21st chromosome. Parents of individuals with DS and ethnically matched controls were enrolled for comparison. Informed written consent was obtained for participation. Peripheral blood was used for isolation of genomic DNA. Target genetic loci were studied by DNA sequence analysis. Data obtained was subjected to population- as well as family-based statistical analysis. rs2270668 was found to be nonpolymorphic in the studied population. rs2270669 showed significant association of the ‘C’ allele and ‘CC’ genotype with DS probands having MH (P=0.02). Computational analysis showed that rs2270669 may induce structural and functional alterations in the COL 3 (VI). Interaction of COL3 (VI) with different proteins, crucial for muscle integrity, was also noticed by computational methods. This pioneering study on COL6A3 with DS related MH thus indicates that rs2270669 ‘C’ could be considered as a risk factor for DS related MH.